ANALISIS SENSIVITAS MODEL PENUGASAN DENGAN METODE HUNGARIAN - TSANI, ELFRIDA RIANI; TASTRAWATI, NI KETUT TARI; SARI, KARTIKA (E-Jurnal Matematika; Vol 10 No 1 (2021), 2021)
In linear programming the assignment problem can be solved by the Hungarian method. This method produces an optimal solution for the placement of e mployees on their assignments. The purpose of this research is to determine the sensitivity analysis of the optimal results from the assignment that has been obtained by the Hungarian Method. Sensitivity analysis is used to determine the extent to which changes can occur without changing the optimal decisions that have been obtained. The results of this research obtain interval working time that can be tolerated without changing the optimal decision that has been obtained. So, no matter how much working time of the Employee changes, as long as the change is still within the interval, it does not interfere with the optimal solution that has been obtained previously .